Time to Complication Detection after Primary Pediatric Hypospadias Repair: A Large, Single Center, Retrospective Cohort Analysis - Lucas, Jacob; Hightower, Tyler; Weiss, Dana A.; Van Batavia, Jason; Coelho, Simmona; Srinivasan, Arun K.; Shukla, Aseem R.; Zderic, Steven A.; Kolon, Thomas F.; Zaontz, Mark R.; Canning, Douglas A.; Long, Christopher J. (The Journal of urology, 2020)
Controversy remains within the pediatric urology community regarding adequate duration of followup after hypospadias repair. Some have suggested that minimal long-term followup is necessary due to a low incidence of late complications. The objective of this study was to delineate time to complication detection for primary hypospadias repairs. We queried our prospectively maintained hypospadias database and identified all patients undergoing primary hypospadias repair from June 2007 to June 2018. Patients were excluded if they had undergone primary repair elsewhere or did not have a followup visit. Complications were defined by the need for an additional unplanned surgical procedure. Kaplan-Meier analysis was performed to assess time to complication by degree of hypospadias. A total of 1,280 patients met inclusion criteria, of whom 976 (68.9%) underwent distal, 64 (4.9%) mid shaft and 240 (18.8%) proximal hypospadias repair. Complication rates were 10.7% (104 patients), 18.8% (12) and 53.8% (129, p<0.0001) for distal, mid shaft and proximal hypospadias repair, respectively. Only 47% of complications were detected within the first year postoperatively. Median time to complication for all repair types was 69.2 months (IQR 23 to 131.9), ie 83.1 months (IQR 42.0-131) for patients undergoing distal repair and 29.4 months (IQR 11.9 to 82.1) for patients undergoing proximal repair (p <0.001). In our large single institution series of pediatric patients undergoing hypospadias repair fewer than half of the complications presented within the first year postoperatively. Long-term followup is recommended for patients undergoing hypospadias repair to adequately detect and address complications.